SOCIALIZATION OF DIABETES MELLITUS PREVENTION IN YOUNG PEOPLE THROUGH THE USE OF HERBAL MEDICINE AT THE ARROHYATI AL FURQON ORPHANAGE - Novi Puspitasari, Renny; Handayani; Sofaria Munir , Ratna; Choirotussanijjah (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2025)
Background Socialization is a process of learning about everything in life, an obligation for parents, society, and the government to teach it to children. The increasing prevalence of obesity in young people is comparable to the increasing proportion of NIDDM cases in young people. Many Indonesian plants are used as medicine for diabetes mellitus, including brotowali (Tinospora crispa), cinnamon (Cinnamomum burmanii Nees), bitter melon (Momordica charantia), and salam (Syzygium polianthum weight). Method Disseminating knowledge about triggers, prevention, and herbal ingredients found around us that can be used to prevent diabetes mellitus. The pre-test and post-test were used to determine the effectiveness of the socialization material. The activity continued with a health checkup, which included a Body Mass Index (BMI) assessment for the foster children. Results and discussion There was an increase in the average score of 21.8 after the socialization activity. This indicates an increase in participants' understanding of the material presented. The pre-test score was 68.2 and the post-test score increased significantly to 90. The results of the Body Mass Index (BMI) examination showed a fairly varied distribution of participants' nutritional status, namely severe obesity 6.25%, obesity 12.5%, healthy weight 50%, underweight 31.25%. Conclusion There was an increase in knowledge among participants after the presentation of the material, indicated by an increase in the average test score of 21.8 compared to the previous session. The health examination results showed that the majority of foster children (50%) had a BMI classified as healthy weight, 31.25% as underweight, 12.5% ​​as obese, and 6.25% as severely obese.